Improving Social Relationships in Peer Relationships among Students Through Group Guidance Services - Aminah Daulay; Herman Nirwana; Rezki Hariko (Journal Of Psychology, Counseling And Education, 2026)
Social relationships within peer groups are a crucial factor in students' academic and personal success. Good relationships enable students to fully realize their potential. However, many students experience difficulties interacting, such as feeling isolated, easily offended, and even having communication problems via social media. This article represents a best practice conducted by researchers. The activity was conducted in a single meeting, focusing on social relationships within peer groups. This best practice study found that students were quite active in participating in group guidance services, beginning with a game of names played by all group members. Group guidance, using a Cognitive Behavior Therapy (CBT) approach, employing cognitive restructuring techniques and discussion strategies, improved students' understanding of social relationships and helped them develop their potential. Students became more active, less awkward or shy about speaking in front of others, and more open, which directly improved the quality of their interactions with peers.